2001
DOI: 10.1046/j.1365-2958.2001.02407.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo nucleotide exchange directed by chimeric RNA/DNA oligonucleotides in Saccharomyces cerevisae

Abstract: SummaryTargeted gene repair directed by chimeric RNA/DNA oligonucleotides has proven successful in eukaryotic cells including animal and plant models. In many cases, however, there has been a disparity in the levels of gene correction or frequency. While the delivery of these chimera into the nucleus and the long-term stability or purity of these molecules may contribute to this variability, understanding the molecular regulation of conversion is the key to improving or stabilizing frequency. To this end, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Therefore to optimise gene correction, we created a reporter system that allows us to measure gene repair directly in living cells. Gene repair reporters have proved effective [11][12][13][15][16][17][18][19][20][21][22] and we hope that this system will allow application of this technology to living cells (see also Liu et al 14 ). A single base substitution was introduced into the EGFP gene (from Clontech's pHygEGFP vector (Clontech, Palo Alto, CA, USA)) to create a premature stop codon (GFP W399X) which inactivates the green fluorescence of EGFP.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore to optimise gene correction, we created a reporter system that allows us to measure gene repair directly in living cells. Gene repair reporters have proved effective [11][12][13][15][16][17][18][19][20][21][22] and we hope that this system will allow application of this technology to living cells (see also Liu et al 14 ). A single base substitution was introduced into the EGFP gene (from Clontech's pHygEGFP vector (Clontech, Palo Alto, CA, USA)) to create a premature stop codon (GFP W399X) which inactivates the green fluorescence of EGFP.…”
Section: Resultsmentioning
confidence: 99%
“…Oligonucleotides were single-stranded 53-mers with the last four bases on each end protected by phosphorothioate linkages (Figure 1). The length and ends were based on the optimization in Igoucheva et al 4 Figure 1) similar to the approach of Rice et al 30 Plasmids were linearized at the MfeI site, purified by phenol chloroform extraction, and electroporated into AB2.2 ESC cells at 30 mg per 8 million cells. The electroporated cells were plated in dishes for selection.…”
Section: Better Design Rules Required To Address Reliability Issuesmentioning
confidence: 99%
“…The repair phase itself may consist of two separate events: the first, the correction of the targeted strand is followed by a second reaction in which the newly modified strand serves as a template to alter the non-targeted strand. Mechanistic studies of TNE have revealed that a number of repair proteins play a role in the correction process by acting through various pathways that include mismatch repair (MMR), and nucleotide excision repair (NER) (ColeStrauss et al, 1999;Dekker et al, 2003;Rice et al, 2001). …”
Section: Introductionmentioning
confidence: 99%